INDUKSI TUNAS IN VITRO DARI TUNAS BATANG (Sucker) TANAMAN NANAS (Ananas comosus (L.) Merr.) ASAL KAMPAR DENGAN PENAMBAHAN 6-BENZYLAMINOPURINE (BAP) - Sari, Risna Manda; Lestari, Wahyu; Fatonah, Siti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Pineapple (Ananas comosus (L.) Merr.) is a fruit plant that is liked most people. Fruitproduction and seedling availability have to be balanced in order to provide consumer’sneed. This problem can be solved using an in vitro technique. This research usedGroup Randomized Design (GRD) Factorial with two factors which are concentrationof BAP and explant section. The concentrations of BAP used in this study were 0,0;0,5; 1,0; 1,5; 2,0; 2,5 mg/l on MS medium. Explant source was collected from sucker,with two different parts whole bud and bud sectioned longitudinally. The objectives ofthis research were to get the optimal concentration, the best explant's cut part, and to getthe best treatment interaction and combination for in vitro shoot induction. The resultshowed that the whole bud that could give response to BAP was indicated by shootformation. The shoot was formed in the percentage of 25% with concentration 1,0 mg/lon 12 th day.